Small diameter hole profile measuring system and calibration method for contactless sensor with fine fiber probe. (December 2021) - Morii, Hideki; Masuta, Hikaru; Watanabe, Tatsuro; Kimura, Hiroaki; Moriyama, Katsufumi; Sekimoto, Michihiro; Terakado, Haruka
Abstract: We developed a system to measure the internal profile of small diameter hole. The minimum measurable diameter is 0.14 mm and the maximum measureable depth is 2 mm. The system can measure the roundness, straightness, cylindricity, and roughness. The main difficulty to measure the small diameter hole is in the relative positioning and aligning between hole and sensor probe. We discuss the principle of alignment, and also the calibration method for the sensor with fine fiber probe.